A Cross-Protective Vaccine Against 4b and 1/2b Listeria monocytogenes - Meng, Fanzeng; Zhu, Tengfei; Yao, Hao; Ling, Zhiting; Feng, Youwei; Li, Guo; Li, Jing; Sun, Xinyu; Chen, Jiaqi; Meng, Chuang; Jiao, Xin’an; Yin, Yuelan (Frontiers in Microbiology, 2020)
Listeria monocytogenes (Lm) is a foodborne zoonotic pathogen that causes listeriosis with a mortality rate of 20%-30%. Serovar 4b and 1/2b isolates account for most of listeriosis outbreaks, however, no listeriosis vaccine is available for either prophylactic or therapeutic use. Here, we developed a triple-virulent-genes deleted vaccine candidate strain, and evaluated its safety, immunogenicity, and cross-protective efficiency. The virulence of NTSN ΔactA/plcB/orfX was reduced 794-fold compared with the parental strain. Additionally, it was completely eliminated in mice at day 7 post infection and no obvious pathological changes were observed in the organs of mice after prime-boost immunization for 23 days. These results verify high safety of the attenuated strain. More importantly, the NTSN ΔactA/plcB/orfX strain stimulated higher anti-Listeriolysin O (LLO) antibody, induced significantly higher expression of IFN-γ, TNF, and IL-6 than the control group, and afforded 100% protection against serovar 4b and 1/2b challenges. Taken together, our research demonstrates that the triple mutation vaccine has high safety, can elicit both a strong Th1 type cellular immune response and humoral immune response, and affords efficient cross-protection against two infectious Lm serotypes. It is a promising vaccine for listeriosis prevention.